THE DEVELOPMENT OF CARE MODEL FOR STROKE PATIENTS WITH DYSPHAGIA, CHUMPHON KHET UDOMSAKDI HOSPITAL, CHUMPHON PROVINCE - Nubanjong, Bangon (Journal of MCU Nakhondhat, 2023)
This research and development the objective were to develop a model and evaluate the use of a care model for stroke patients with dysphagia. Sample specifically selected, there are 4 groups : 7 person developed the model, 12 nurses who use the model,72 patients and 72 caregiver. Develop the pattern according to the clinical practice guidelines for dysphagia patient of the medical department. In collaboration with 7 Aspects of care and discharge planning. The tool used in this research were observation, focus group, model of care for stroke patients with dysphagia, assessment form nurse opinion on the use of the model, knowledge test and practice assessment form of nurse, knowledge test and practice assessment form of caregiver, assessment level of swallowing ability, record about aspirate pneumonia. The data were analysis using frequency distribution, percentage, mean, and standard deviation. Paired t – test and qualitative data analysis. The results showed that the pattern users commented that the pattern developed with a probability of 95.77%. Patients had improved swallowing ability by week 1, 2, 4, 8, 12 have a number 6.94,31.94,54.17,68.06,70.83 % respectively and no aspirate pneumonia. Nurse have more knowledge and practice with statistical significance at the lavel of 0.05. caregiver have more knowledge and practice with statistical significance at the lavel of 0.05. The research results suggest that care of patients with dysphagia requires a developed model that will benefit the patient quality of life.